Nivel de conocimiento y prácticas de manejo de residuos sólidos en pobladores del AAHH “Frank Saboya”. Punchana. Loreto. 2024 - Suarez Gomez, Aldo Alfredo (2025)
This research aimed to study the relationship between solid waste management knowledge and practices among residents of the Frank Saboya 2024 AAHH. The research approach was quantitative, prospective, simple relational, and non experimental. The target population for the study consisted of 420 residents who were living there in 2024. The sample also consisted of 74 residents who were present at the time of the data collection instrument. Inclusion and exclusion criteria were taken into account. The technique used was a survey, and the instrument applied was a 20 statement questionnaire, which passed validity tests (Aiken's validity index) and reliability tests (Cronbach's alpha test). The data obtained through the data collection instrument were analyzed based on the research objectives and hypothesis, and subsequently expressed. The data were compiled in a Basic Data Matrix (BDM) and analyzed, processed, and tabulated using the SPSS version 27 statistical package. The main results showed a generalized deficit in knowledge about solid waste management. Formal education does not guarantee practical environmental competencies, since, despite some residents having higher education, their knowledge about solid waste management does not show significant improvements compared to other educational levels. There is a disconnect between knowledge and practice; despite a mostly "fair" knowledge of solid waste management, adequate practices are prevalent, suggesting that factors such as community habits and local programs significantly influence environmental practices.